Perbedaan Jumlah Trombosit Pasca Transfusi Thrombocyte Concentrate Dan Thrombocyte Apheresis Pada Pasien Trombositopenia - Rudina Azimata Rosyidah; Novia Anjani; Windadari Murni Hartini; Ana Mardiyaningsih (Jurnal Kesehatan, 2023)
Thrombocytopenia is a condition when the number of platelets is below normal. Several types of platelet blood component transfusions include Thrombocyte Concentrate and Thrombocyte Apheresis. Platelet blood components for transfusion can be obtained from two methods, namely the method of processing Whole Blood (WB) and the apheresis method. Thrombocyte Concentrate Transfusion and Thrombocyte Apheresis Transfusion are forms of using blood components as a supportive measure to increase the platelet count of thrombocytopenic patients. This study aims to determine the difference in platelet count after Thrombocyte Concentrate and Thrombocyte Apheresis transfusions in thrombocytopenic patients. The research method used is Analytical Descriptive with a Cross Sectional research design. The population in this study were thrombocytopenia patients, totaling 66 patients. The samples used in this study were 28 samples of thrombocytopenic patients, consisting of 14 patients receiving Thrombocyte Concentrate transfusions and 14 patients receiving Thrombocyte Apheresis transfusions which were obtained using the Purposive Sampling technique. Data were analyzed univariately and bivariately using the independent t test. The results of this study indicated that the difference in platelet count after Thrombocyte Apheresis transfusion was higher than after Thrombocyte Concentrate transfusion. The average increase in platelet count after Thrombocyte Apheresis transfusion was 49,286/µl while in Thrombocyte Concentrate transfusion it was 20,143/µl.